(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aimed to explore the role of the teachers of basic teaching stage in developing the comprehension reading skills of pupils , by using variety and appropriate activities for each sort of skills. It also aimed to determine the sorts of skills that get the most and the least interest by the teachers, and to know what the favorite instructional strategies that teachers prefer to develop the comprehension reading skills of their pupils , and discovering the impact of the years of experience in teaching on their using comprehension reading skill alone. According to that , the descriptive approach was adhered . So a special questionnaire – consisted of (30) items in three fields was designed for that purpose. The sample of this research was selected randomly and consisted of (120) teachers who have a license in education (class room teacher). The research’s results show the positive role of the teachers of basic teaching stage in developing comprehension reading skills of their pupils in general. The skills of ’paragraph level’ has got the greatest interest, then the skills of ’sentence level’ and the skills of the ’word level. Whereas the study doesn’t show any statistical different among the average of the degrees of teachers in developing the comprehension reading skills according to the years of experience in teaching . This study recommended to include the curricula suitable activities of all these skills, and execution studies that aimed to explore what the most important instructional strategies that contributes in developing the comprehension reading skill.